Optimasi Menu Makanan Untuk Pemenuhan Gizi Penderita Kanker Dengan Algoritme Genetika - Dellia Airyn; Imam Cholissodin; Budi Darma Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
One of the most feared disease in the world today is cancer. For cancer patients, various ways have been done, one of them is chemotherapy. But in chemoteraphy, patients will experience digestive and absorption of nutrients disorder, thus affecting the nutritional status of patients. So, the menu orders for cancer patients become the most important thing to reduce the side effect of chemoteraphy, especially in term to fulfill the needs of energy and protein. In this study, there are 111 food menu, consist of 31 foods source of carbohydrate, 34 foods source of animal protein, and 46 foods source of plant protein.The method in this study using genetic algorithm, which is an optimization algorithm that similar to evolution theory in case determining the chromosomes or individual.The representation used is a permutation representation, with One-Cut Point Crossover and Reciprocal Exchange Mutation methods. The results and analysis of crossover rate and mutation rate combination against the average fitness value showed 0,6;0,4 has the largest average value, which is 762,19. In population test, the highest average fitness score was 631,16 in the 300th population. While in generation test, the highest average fitness value was 666,22 in the 200th generation.